2021
DOI: 10.1111/1748-8583.12417
|View full text |Cite
|
Sign up to set email alerts
|

Human resources analytics: A legitimacy process

Abstract: Taking a grounded theory approach, this paper explores human resources (HR) Analytics legitimacy in three organisations over a period of 3 years. The research aims to investigate (i) how the HR Analytics legitimacy process presents and develops and (ii) what decisions, activities, and events can shape the legitimacy of HR Analytics in organisations. We draw on institutional theory and industry creation literatures to understand what constitutes HR Analytics legitimacy through a three‐dimensional perspective: c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 50 publications
1
17
0
1
Order By: Relevance
“…It also involves selling HR analytics as a whole by HR analysts to stakeholders more broadly to advance the HR analytics agenda in organisations at a policy level. Recent studies address this to some extent in highlighting the institutional work involved in gaining legitimacy for HR analytics (Belizón & Kieran, 2021; Ellmer & Reichel, 2021). We build on this work to draw attention to the advocacy and ambassadorial work HR analysts engage in to win support for the broader policy agenda, often driven by their own professional goals and interests and/or stimulated by the expectations of their leaders to promote a policy where HR decisions are made based on data and insights derived from analytics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also involves selling HR analytics as a whole by HR analysts to stakeholders more broadly to advance the HR analytics agenda in organisations at a policy level. Recent studies address this to some extent in highlighting the institutional work involved in gaining legitimacy for HR analytics (Belizón & Kieran, 2021; Ellmer & Reichel, 2021). We build on this work to draw attention to the advocacy and ambassadorial work HR analysts engage in to win support for the broader policy agenda, often driven by their own professional goals and interests and/or stimulated by the expectations of their leaders to promote a policy where HR decisions are made based on data and insights derived from analytics.…”
Section: Discussionmentioning
confidence: 99%
“…To this extent, HR analysts need to promote the concept and use cases of HR analytics to inform business decisions. The concept of entrepreneurial legitimacy (Aldrich & Fiol, 1994) is used by Belizón and Kieran (2021) in their discussion of institutional work involved in the introduction and development of HR analytics in three case companies. They argue that the uptake and advancement of HR analytics projects is related to decisions and events that influence whether and how HR professionals attain legitimacy for their knowledge (also referred to as cognitive legitimacy), their position in HR analytics projects (also referred to as socio‐political legitimacy) and in terms of the technology use underpinning analytics (also referred to as technological legitimacy).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Their longitudinal inquiry showed that a series of accelerating, enabling and delaying elements have variously influenced the cognitive, sociopolitical and technological legitimacy of three HRA subprocesses, namely the strategic commitment of HRA, the focus of HRA projects and the HR data infrastructure decision. While companies may pull different levers to legitimate the development of HRA, their data suggest “a relatively slow growth in HRA legitimacy over the course of 3 years” (Belizon and Kieran, 2021, p. 14).…”
Section: Human Resource Analytics: the Theoretical Normative And Crit...mentioning
confidence: 99%
“…Highlighting the complexity of adopting, implementing and delivering greater value through HRA, Belizon and Kieran (2021) used a grounded theory approach among HRA practitioners in three Irish-based companies to uncover the factors at play in the development of the HRA legitimacy process. Their longitudinal inquiry showed that a series of accelerating, enabling and delaying elements have variously influenced the cognitive, sociopolitical and technological legitimacy of three HRA subprocesses, namely the strategic commitment of HRA, the focus of HRA projects and the HR data infrastructure decision.…”
Section: Introductionmentioning
confidence: 99%